Should banks be worried about dividend restrictions? - Josef Schroth (Bank of Canada, 2023)
Countercyclical bank capital requirements have emerged as a popular regulatory tool to help smooth financial cycles. The idea is to reduce capital requirements when exogenous shocks cause aggregate bank capital to decrease so that regulation does not needlessly constrain banks' supply of credit. In the model in this paper, banks are rationally forward-looking and thus ignore short-lived reductions in capital requirements. During a financial crisis, a regulator would want to first impose drastic dividend restrictions to force banks to rebuild capital, but also would want to keep capital requirements low for a sufficiently long time afterwards. However, such a policy is not time-consistent. Once banks are sufficiently re-capitalized, the regulator would be tempted to immediately raise capital requirements all the way to pre-crisis levels. Optimal time-consistent capital regulation requires that bank capital is rebuilt gradually during financial crises. In particular, banks must be able to pay dividends even when bank equity is still significantly below pre-crisis levels.
Keywords: E1; E13; E3; E32; E4; E44; 330; Business fluctuations and cycles; Credit and credit aggregates; Credit risk management; Financial stability; Financial system regulation and policies; Lender of last resort